(untitled) (Argos, 2025)
This article points out in its first part, appeared in this same journal, the great interest for linguistic studies manifested by India, and exposes the knowledge accumulated in India before the VIth century B.C. in Sanskrit phonetics, etymology and grammar. Then it deals with the contributions of Yāska to the science of etymology and, in this second part, with those of Pāṇini to the science of grammar, and ends with a brief reference to Kātyāyana and Patañjali, the great commentators of Pāṇini. The article includes, in this second part, an example of Pāṇini’s method analyzing his rules on the intensive mode.